2022
DOI: 10.1136/annrheumdis-2022-eular.5054
|View full text |Cite
|
Sign up to set email alerts
|

Pos0577 comparison of the Who and Acc/Aha Cardiovascular Algorithms to Detect Carotid Plaque in Rheumatoid Arthritis

Abstract: BackgroundCardiovascular disease is the major cause of death in rheumatoid arthritis (RA) patients. Cardiovascular risk algorithms are used to estimate the probability for the development of a cardiovascular event in 10 years, according to patients’ characteristics, however, no algorithm existed for the Hispanic population until the World Health Organization (WHO) published the cardiovascular disease risk charts for 21 regions (1).ObjectivesTo compare the capacity of the 2019 WHO algorithm and the 2013 America… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A prior study supported the World Health Organization’s 1994 publication which found that rheumatic patients had a higher risk of developing osteoporosis and osteopenia [ 2 ]. Furthermore, RA patients are at high risk for the development of cardiovascular complications considering the recent 2019 WHO and the 2013 American College of Cardiology and American Heart Association’s (ACC/AHA) published reports [ 3 ]. Although the triggering cause of RA is unclear, it is assumed to be a product of genetic and environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…A prior study supported the World Health Organization’s 1994 publication which found that rheumatic patients had a higher risk of developing osteoporosis and osteopenia [ 2 ]. Furthermore, RA patients are at high risk for the development of cardiovascular complications considering the recent 2019 WHO and the 2013 American College of Cardiology and American Heart Association’s (ACC/AHA) published reports [ 3 ]. Although the triggering cause of RA is unclear, it is assumed to be a product of genetic and environmental factors.…”
Section: Introductionmentioning
confidence: 99%